2012
DOI: 10.3109/08923973.2011.630008
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of diethylcarbamazine on humoral, cellular cytokine response and respiratory burst in BALB/c mice

Abstract: Diethylcarbamazine (DEC) is an anthelmintic piperazine derivative drug with putative immunomodulating properties, including increased platelet and granulocyte adhesion to parasites and enhanced production of cytokines. To further analyse these properties in a well-established animal model, we evaluated the effect of DEC on antibody, cellular cytokine response and respiratory burst in BALB/c mice. Animals were challenged with a thymus-dependent (tetanus toxoid, (TT)) and with a thymus-independent (lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
3
11
1
Order By: Relevance
“…Thus, the acquired immunity may control bacterial growth and help to eliminate bacteria and resist to infection, thus inhibiting a further development of lesion. Although an increased production of antibodies under DEC treatment has been shown before [9,10], we did not find any correlation between IgG and IgM antibody production and the protection given by DEC administration. Resistance to intracellular microorganism infections involves most immune effectors and principally T cells.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Thus, the acquired immunity may control bacterial growth and help to eliminate bacteria and resist to infection, thus inhibiting a further development of lesion. Although an increased production of antibodies under DEC treatment has been shown before [9,10], we did not find any correlation between IgG and IgM antibody production and the protection given by DEC administration. Resistance to intracellular microorganism infections involves most immune effectors and principally T cells.…”
Section: Discussioncontrasting
confidence: 81%
“…The influence of DEC in an infectious model produced by N. brasiliensis seems to confirm in vivo the positive immunomodulatory effect observed earlier where oxidative burst was increased in both monocytes and granulocytes after DEC therapy [10]. In spite of it, in our actual study although an enhancement of monocyte oxidative index was not demonstrated in vitro, the striking modification of the lesion was evident, suggesting an in vivo action on cellular effectors of host after drug administration [10].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…DEC has already been shown to possess immunomodulatory effects in respiratory burst in BALB/c mice [19], bacterial and fungal infections [11]. In viral infections such as feline leukemia virus (FeLV) in cats [10] and Human Immunodeficiency Virus (HIV) [9], DEC has exhibited adjuvant effect by enhancing the humoral and cellular response towards elimination of the virus.…”
Section: Discussionmentioning
confidence: 99%